Peran Guru Agama Katolik di SLB-A Karya Murni Medan - Sukma kusuma dewa; Diah ayu lestari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Teaching Catholic Religious Education (CRA) classes to blind children is not easy. Qualified teachers who know how to handle children with special needs, such as the blind. The research